Des femmes, des hommes et des rumeurs. Hommes machos et femmes stigmatisées/antes dans une ville de tourisme sexuel - Denise Brennan (Genre, Sexualité et Société)
This article focuses on gossip about Dominican women sexual labor as an entry point into documenting shifting gender relations and ideologies in Sosúa, a sex tourist destination frequented primarily by German tourists. In Sosúa sexscape, new meanings of masculinity have emerged alongside women earning capacity. While sex workers must temper their displays of monetary gains so as to not compromise their reputations as mothers sacrificing for their children, men openly enjoy freedom from gender ideologies that make demands on them to appear as hard working and sacrificing fathers. In this sexual economy, men even can flaunt their unemployment. Their laziness and/or dependency are recast as macho. Here is one industry where poor Dominican women have the opportunity to make significant earnings and to jump out of poverty, yet their labor strategies do not necessarily ensure a reconfiguration of gender roles and ideologies that works in their favor. Rather, migrant men in Sosúa enjoy such a reworking that lowers expectations for them, while women are caught in a set of increased expectations.